2019
DOI: 10.3928/00220124-20191015-06
|View full text |Cite
|
Sign up to set email alerts
|

Stop the Bleed Training Improves Knowledge, Skills, and Confidence Among School Nurses

Abstract: Background: School nurses play an integral part in prehospital care for life-threatening bleeding in educational environments. This study evaluated the efficacy of Stop the Bleed training for improving school nurses' knowledge, hands-on skill, self-confidence, and belief in school preparedness for responding to a life-threatening bleeding emergency. Method: Sixteen northeastern U.S. public school nurses completed a 1-hour seminar on appropriate life-thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 9 publications
3
11
0
2
Order By: Relevance
“…The study showed that those who had first aid training had 2.12 higher odds of correct tourniquet application and those who had bleeding control training had 3.5 higher odds of correct applications compared with those with no training [22]. These results also reported by other studies that showed increase in confidence and knowledge in bleeding control after having training [23][24][25][26].…”
Section: Discussionsupporting
confidence: 72%
“…The study showed that those who had first aid training had 2.12 higher odds of correct tourniquet application and those who had bleeding control training had 3.5 higher odds of correct applications compared with those with no training [22]. These results also reported by other studies that showed increase in confidence and knowledge in bleeding control after having training [23][24][25][26].…”
Section: Discussionsupporting
confidence: 72%
“…Yet, to date only one study has examined STB within an educational environment (Latuska et al, 2019). Due to a small sample size and the participants having preexisting medical knowledge (school nurses) in the aforementioned study, it was difficult to determine how STB improved high school personnel’s perception of school safety and preparedness in case of school violence (Latuska et al, 2019). This is especially important to consider when assessing perceptions of school preparedness since school nurses may have differing points of view from other high school personnel without a medical background.…”
Section: Introductionmentioning
confidence: 99%
“…After completion of a 1-h STB training, increases in knowledge, hands-on skills (wound packing and tourniquet application), and identification of cases of life-threatening bleeding were significantly improved. Prior to the training, most nurses felt relatively neutral about their ability to respond to a life-threatening bleeding emergency, but following the training almost all agreed or strongly agreed that they were confident in their ability to respond to a life-threatening bleeding emergency [13]. This indicates that a basic STB training not only enhances knowledge and skills as previously discussed, but also could be used to improve more intrinsic factors such as self-confidence.…”
Section: Improvement Of Confidence Preparedness and Willingness To mentioning
confidence: 70%
“…For this reason, several groups have examined how the attainment of knowledge and skills affect the attitudes of bystanders to provide help. Latuska et al conducted a study to look at these concepts, specifically using a population of school nurses [13]. After completion of a 1-h STB training, increases in knowledge, hands-on skills (wound packing and tourniquet application), and identification of cases of life-threatening bleeding were significantly improved.…”
Section: Improvement Of Confidence Preparedness and Willingness To mentioning
confidence: 99%